A theranostic nanoplatform: magneto-gold@fluorescence polymer nanoparticles for tumor targeting T1&T2-MRI/CT/NIR fluorescence imaging and induction of genuine autophagy mediated chemotherapy. Issue 22 (25th May 2018) - Wang, Guannan; Qian, Kun; Mei, Xifan
Abstract : Novel contrast agent were designed for in vivo T1 &T2 -MRI/CT/NIR fluorescence imaging and induction of genuine autophagy-mediated chemosensitization for cancer therapy. Abstract : Multifunctional nanoparticles, bearing low toxicity and tumor-targeting properties, coupled with multifunctional diagnostic imaging and enhanced treatment efficacy, have drawn tremendous attention due to their enormous potential for medical applications. Herein, we report a new kind of biocompatible and tumor-targeting magneto-gold@fluorescent polymer nanoparticle (MGFs-LyP-1), which is based on ultra-small magneto-gold (Fe3 O4 -Au) nanoparticles and NIR emissive fluorescent polymers by a solvent-mediated method. This kind of nanoparticle could be taken up efficiently and simultaneously serve for in vivo tumor targeting T 1 & T 2 -MRI/CT/near infrared (NIR) fluorescence bioimaging. Furthermore, the nanoparticles exhibit small size, higher tumor targeting accumulation, excellent cytocompatibility for long-term tracking, and no disturbing cell proliferation and differentiation. Moreover, clear and convincing evidence proves that as-synthesized MGFs-LyP-1 could elicit genuine autophagy via inducing autophagosome formation, which offers a definite synergistic effect to enhance cancer therapy with doxorubicin (DOX) at a nontoxic concentration through enhancement of the autophagy flux. Meanwhile, the as-prepared nanoparticles could be rapidly cleared from mice without any obvious organ impairment. The results indeed reveal a promising prospect of an MGFs-LyP-1 contrast agent with low toxicity and high efficiency for promising application in biomedicine.